Students’ Interest and Attitudes in Learning Arts and Culture in Elementary School: Minat dan Sikap Siswa dalam Pembelajaran Seni dan Budaya di Sekolah Dasar - Sulfiana, Nadia; Darmawan K. W, Mahardika (Indonesian Journal of Education Methods Development, 2025)
General Background: Learning interest and attitudes are central to students’ engagement and classroom behavior in elementary education. Specific Background: Arts and culture subjects in primary schools are often considered secondary, leading to limited attention despite their role in fostering creativity and participation. Knowledge Gap: Few studies describe how students’ learning interest aligns with observable learning attitudes in arts and culture classes at the elementary level. Aim: This study describes the learning interest and learning attitudes of fourth- and fifth-grade students toward arts and culture subjects. Results: Findings show that most students in both grades demonstrate high to very high interest, with fifth-grade students showing more consistent alignment between interest and appropriate learning attitudes. Observations indicate variations in aspects such as creativity, cooperation, discipline, and responsibility, particularly among fourth-grade students. Novelty: The study integrates questionnaire data on learning interest with structured observations of learning attitudes across multiple behavioral indicators in an elementary arts context. Implications: The results provide practical insights for teachers to adjust classroom strategies and better support students’ engagement and behavioral development in arts and culture learning. Highlights Fifth-grade students show stronger consistency between interest and learning attitudes. Creativity and cooperation remain areas needing improvement, especially in fourth grade. Combined use of questionnaires and observation offers a fuller view of student behavior. Keywords: Learning Interest; Learning Attitudes; Arts And Culture Education; Elementary Students; Classroom Behavior